PERAN KELUARGA DALAM PELAKSANAAN INISIASI MENYUSU DINI DAN PEMBERIAN KOLOSTRUM PADA BUDAYA MADURA DI KABUPATEN JEMBER - Riza Umami (Jurnal Informasi Kesehatan Indonesia (JIKI), 2019)
Implementation of early breastfeeding initiation (IMD), giving colostrum at the beginning ofa baby’s life to exclusive breastfeeding for the first six months can reduce morbidity and mortality ininfants. Encouragement / support and advice from close people and family members to seek treatmentwill have a major influence on the desire and motivation to get health services. The purpose of this studywas to identify the role of the family in the implementation of IMD and the administration of colostrumin the culture of Madura (Pandalungan). The research method used is analytic survey with a case studyand field research approach. The population is postpartum mothers aged> 4 days. The results of thestudy stated that there was a relationship between the role of the family in the implementation of the IMDand the administration of colostrum with sufficient strength.